Russia, BRICS, and the disruption of global order - Salzman, Rachel S. (Georgetown University Press, 2019)
Russia's leadership in establishing the BRICS group (Brazil, Russia, India, China, and South Africa) is emblematic of its desire to end US hegemony and rewrite the rules of the international system. Rachel S. Salzman tells the story of why Russia broke with the West, how BRICS came together, why the group is emblematic of Russia's challenge to the existing global order, and how BRICS has changed since its debut. The BRICS group of non-Western states with emerging economies is held together by a shared commitment to revising global economic governance and strict noninterference in the internal affairs of other countries. BRICS is not exclusively a Russian story, but understanding the role of BRICS in Russian foreign policy is critical to understanding the group's mission. In a time of alienation from the Euro-Atlantic world, BRICS provides Russia with much needed political support and legitimacy. While the longterm cohesion of the group is uncertain, BRICS stands as one of Vladimir Putin's signature international accomplishments. This book is essential reading for scholars and policymakers interested in Russian foreign policy, the BRICS group, and global governance.